2022
DOI: 10.35848/1347-4065/ac67ba
|View full text |Cite
|
Sign up to set email alerts
|

Study on deprotonation from radiation-induced ionized acrylate polymers including acid-generation promoters for improving chemically amplified resists

Abstract: The demand for improved performance of chemically amplified resists (CARs) is continually increasing with the development of extreme ultraviolet lithography. Acid-generation promoters (AGPs) increase the sensitivity of CARs by increasing the initial acid yield immediately after the exposure process. However, the detailed mechanism of acid-yield enhancement has not been clarified yet. Deprotonation from the ionized polymer (i.e., radical cations) is an important reaction to assess acid generation. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…We have previously shown that the initial acid yield prior to PEB can be increased by 10%-20% by adding 12 wt% DTS to P1-4. 32) The resist sensitivity increased 1.7 to 7.5 times more with 10 wt% DTS addition than without. This indicates that the effectiveness of DTS is greater than the degree of increase in the initial acid yield.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We have previously shown that the initial acid yield prior to PEB can be increased by 10%-20% by adding 12 wt% DTS to P1-4. 32) The resist sensitivity increased 1.7 to 7.5 times more with 10 wt% DTS addition than without. This indicates that the effectiveness of DTS is greater than the degree of increase in the initial acid yield.…”
Section: Resultsmentioning
confidence: 93%
“…We have shown that the initial acid yield of the polymers is on the order of P4 > P3 > P2 > P1. 32) By contrast, EUV sensitivity is on the order of P1 > P4 > P3 > P2. Thus, P1 has the highest sensitivity despite its lower initial acid yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of CAR has been altered such that the mechanism for light-mediated solubility modulation became valid with different light sources including DUV and EUV. The CAR system has been optimized for lithographic techniques using KrF and ArF excimer lasers; however, in EUV lithography, one challenging issue still remains to be addressed: trade-off relationship among resolution, line edge roughness (LER), and sensitivity, the-so-called RLS trade-off. Different chemistries have been proposed to resolve this issue; however, because of the strong compatibility of CARs with the current semiconductor device fabrication process, CAR still remains an important candidate for single-digit nanometer technical nodes with EUV lithography. …”
Section: Introductionmentioning
confidence: 99%
“…2 The requirement of thin resists in EUV lithography further exacerbates the problem. One approach to improve CARs' performance in EUV is to add more photoacid generators in the resist, 3,4 which has limited success. Inorganic resists, in particular metal oxides, which are not used in DUV lithography are studied as potential EUV resists because elements such as metals, semimetals, and transition metals have larger EUV absorption cross-sections than carbon.…”
Section: Introductionmentioning
confidence: 99%